Bases biológicas para utilização de Trichospilus diatraeae (Hymenoptera: Eulophidae) para controle de Helicoverpa armigera (Lepidoptera: Noctuidae) - Bueno, Nádia Maebara [UNESP] (2015)
Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) is a polyphagous insect, with wild geographic distribution and considered the most important pest in the regions where it occurs. Recently, in the 2013/2014 growing season, its presence was first registered in Brazil, bringing yield loss and therefore economic damages. This species has several characteristics that make it of considerable interest, such as the fact of its capacity in disperse over long distances, caterpillars that feeds of reproductive structures, high fertility and optional diapause pupae. Furthermore, it is a species that is resistant to a large number of insecticides. In this scenario, other control tactics, covering inter and multidisciplinary techniques should be adopted in accordance with the proposal of Integrated Pest Management (IPM). One of them, biological control, has great potential because it does not cause environmental imbalance and can keep the pest population below economic injury level. In this sense, the pupae parasitoid Trichospilus diatraeae Cherian & Margabandhu (Hymenoptera: Eulophidae) presents potential to be utilizated in biological control. T. diatraeae is a widely distributed species in Brazil, and have already been recorded in several Lepidopteran families, which characterizes this insect as highly polyphagous. Therefore, it is necessary to know the interactions between parasitoid and host, making it important to study these characteristics. Thus, the objective of this work was to study the ...